Parâmetros metabólicos e íons plasmáticos de piavas (Leporinus obtusidens) expostas a diferentes níveis de oxigênio dissolvido e amônia - Bolner, Keidi Carolina dos Santos (2007)
Piava juveniles (7-13 cm; 25-30 g) were exposed to different NH3 (mg L-1): 0.003 (control), 0.1, 0.3, 0.7, 1.4, and dissolved oxygen levels (mg L-1): 1.0, 2.0, 3.0, 4.0, and 6.0, for 4 days (96h). Na+, K+, Cl-, and NH4 + plasma levels were measured, as well as metabolics and enzyme activity in tissues (liver, kidney, gills, and muscle). The lethal concentration (LC50-96h) for piava was 0.27 (0.21 0.34) mg L-1 NH3, and Na+ and NH4 + plasma levels increased and K+ decreased with the increase of waterborne NH3 levels. Na+, K+ -ATPase activity increased in the gills and decreased in the kidney with the increase of waterborne NH3 levels. Glucose levels in the liver and muscle decreased as waterborne NH3 concentrations raised. NH4 + levels in the tissues presented a positive correlation with waterborne NH3 levels. Na+, Cl-, K+ and NH4 + plasma levels and Na+, K+ -ATPase activity in the gills increased with dissolved oxygen reduction in the water. Glucose levels in the liver and muscle and ammonia in all tissues also increased with the reduction of dissolved oxygen levels in the water, but glycogen levels decreased. Consequently, ammonia is a stressor agent for this species, leading to an accumulation of ammonia in plasma and other tissues. In piava, hypoxia led to physiological changes in both osmoregulatory and metabolic parameters.